Using 3-D video game technology in channel modeling (2014)
We present here a paper on the potential use of game engines and graphic technologies for 3-D ray-based technologies used to simulate multipath channels. Our approach harnesses the power of video game development engines to provide an urban 3-D ray-based model for exploration and analysis of multipath channels for a wide frequency range in different complex outdoor and indoor scenarios. Game technologies offer a variety of options for exploiting the capabilities of graphical processing units and provide high performance in computing time with accurate results for channel modeling in current and future wireless technologies. We show the usefulness of this approach using our 3-D ray-based system in different applications.